Inventarisasi mycoflora yang berasosiasi dengan biji kopi pada tiga sistem pengolahan dan dua musim panen - Nurdin, Muhammad; Evizal, Rusdi; Ginting, Cipta; Liandari, Rizky Fatma (Jurnal Proteksi Agrikultura, 2025)
This study aims to determine the percentage of the presence of fungi associated with processed coffee beans that freshly harvested and those that have been stored for 6 months and identify the fungi found at least to the genus level. This research was conducted from July to September 2021 at the Agricultural Biotechnology Laboratory, Faculty of Agriculture, University of Lampung. The method used was a survey method. Coffee beans samples were taken in Sedayu Village, Semaka District, Tanggamus Regency. Samples of coffee beans were taken at different season, namely in October 2020 and April 2021. The types of processed coffee that would be identified were natural, honey and lowgrade. The method used in this study was the direct plating method using PSA (Potato Sucrose Agar) media and repeated 5 times by putting 5 coffee beans in each petri dish. The variables in this study were identification of fungi based on their macroscopic and microscopic properties and analysis of  index diversity. The results showed that as many as six fungi were found to be associated with coffee beans, namely, Aspergillus niger, Aspergillus fumigatus, Aspergillus flavus, Aspergillus parasiticus, Phytophthora sp. and Penicillium sp. The most commonly species was found, Aspergillus niger, which was 64% found in processed coffee from the 2021 harvest year. The result of the analysis show that the fungi diversity index (H’) of low grade coffee beans in the 2020 harvest season and natural processed 2021 classified as moderate diversity (1 ≤ H’ ≤ 3). While, other processed products are classified as low diversity (H < 1).